PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV - Rima Safitri; Encep Andriana; Siti Rokmanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is entitled The Role of Teachers in Increasing the Learning Motivation of Class IV Students at SDN Pamarayan 1 Serang Regency. The aim of this research is to determine the Role of Teachers in Increasing the Learning Motivation of Class IV Students at SDN Pamarayan 1 Serang Regency. This research uses qualitative descriptions. The subjects of this research were class IV homeroom teachers, this research was conducted at SDN Pamarayan 1 in 2023. The data collection techniques used in this research were interviews, observation and documentation. The data obtained qualitatively shows that the teacher's role as class manager and also as class IV homeroom teacher is knowing what conditions and how to handle students in class. The teacher's role as a mediator or facilitator. The coordinator asked the class IV homeroom teacher to adapt the media from the RPP. The role of the teacher As an evaluator, the Class IV teacher provides authentic assessments and collects data from summative, formative and evaluative assessments. Everyday life. The role of the class IV homeroom teacher as a motivator is to encourage students to learn through inspirational stories.